Planning for the Next Pandemic: Trauma Injuries Require Pre-COVID-19 Levels of High-Intensity Resources. Issue 6 (June 2022) - Mokhtari, Ava K.; Maurer, Lydia R.; Wong, Yee M.; Hardman, Claire; Hafiz, Shabnam; Sharrah, Mark; Soe-Lin, Hahn; Peralta, Rafael; Parks, Jonathan J.; Rattan, Rishi; Butler, Caroline; Hwabejire, John O.; et al.
As hospital systems plan for health care utilization surges and stress, understanding the necessary resources of a trauma system is essential for planning capacity. We aimed to describe trends in high-intensity resource utilization (operating room [OR] usage and intensive care unit [ICU] admissions) for trauma care during the initial months of the COVID-19 pandemic. Trauma registry data (2019 pre-COVID-19 and 2020 COVID-19) were collected retrospectively from 4 level I trauma centers. Direct emergency department (ED) disposition to the OR or ICU was used as a proxy for high-intensity resource utilization. No change in the incidence of direct ED to ICU or ED to OR utilization was observed (2019: 24%, 2020 23%; P = .62 and 2019: 11%, 2020 10%; P = .71, respectively). These results suggest the need for continued access to ICU space and OR theaters for traumatic injury during national health emergencies, even when levels of trauma appear to be decreasing.